International Neurotrauma Training Based on North-South Collaborations: Results of an Inter-institutional Program in the Era of Global Neurosurgery - Rubiano, Andrés M.; Griswold, Dylan P.; Adelson, P. David; Echeverri, Raul A.; Khan, Ahsan A.; Morales, Santiago; Sánchez, Diana M.; Amorim, Robson; Soto, Alvaro R.; Paiva, Wellingson; Paranhos, Jorge; Carreño, José N.; et al. (Frontiers in Surgery, 2021)
Objective: Shortage of general neurosurgery and specialized neurotrauma care in low resource settings is a critical setback in the national surgical plans of LMICs. Neurotrauma fellowship programs typically exist in HICs, where surgeons who fulfill the requirements for positions regularly stay to practice. Due to this issue, neurosurgery residents and medical students from LMICs do not have regular access to this kind of specialized training and knowledge-hubs. The objective of this paper is to present the results of a established neurotrauma fellowship program for neurosurgeons of LMICs in the framework of global neurosurgery collaborations, including the involvement of specialized parallel education for neurosurgery residents and medical students. Methods: The Global Neurotrauma Fellowship program was inaugurated in 2015 by a collaboration between a HIC and an LMIC. The organizers designed it to be a twelve-month program based on neurotrauma international competencies with the support of the Barrow Neurological Institute at Phoenix Children’s Hospital and Meditech Foundation in Colombia. Since 2018, additional support from the UK, NIHR Global Health Research in Neurotrauma Project from the University of Cambridge enhanced the infrastructure of the program, adding a research component in global neurosurgery and system science. Results: Eight fellows from Brazil, Venezuela, Cuba, Pakistan, and Colombia have been trained and certified via the fellowship program. The integration of competencies and exposure to systems of care in HICs and LMICs environments creates a unique environment for training within a global framework. Additionally, 18 residents (Venezuela, Colombia, Ecuador, Peru, Cuba, Germany, Spain, and the USA), and ten medical students (the United Kingdom, USA, Australia, and Colombia) have also participated in elective rotations of neurotrauma and critical care during the time of the fellowship program, as well as in research projects as part of an established global surgery initiative. Conclusion: We have shown that it is possible to establish a neurotrauma fellowship program in an LMIC based on the structure of HIC formal training programs. Adaptation of the international competencies focusing on neurotrauma care in low resource settings and maintaining international mentoring and academic support will allow the participants to return to practice in their home-based countries.